The Analysis of Farmer's Funds in Determining the Cost of Capital on Rice Farming Business in Loea District Kolaka Timur Regency - Dedi Hermanto; Azhar Bafadal; Samsul Alam Fyka (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Financing is very important for farmers to manage their farming because capital is very important in lowland rice farming. This study aims to determine the financing pattern of lowland rice farming in the Loea District, East Kolaka Regency. This study aims to identify the financing pattern of lowland rice farming in the Loea District, East Kolaka Regency. This research was conducted from July 2021 to February 2022 in Loea District, East Kolaka Regency, Southeast Sulawesi. The population of this study was 241 people. Using simple random sampling where obtained 36 members of the rice farmers who carried out the financing pattern as the research sample was obtained. The variables in this study are the respondent's identity, including age, education, number of family dependents, and farming experience; Financing patterns, including self-financing and partner financing. Data analysis used descriptive qualitative analysis. The results showed that the financing pattern for lowland rice farming in Loea District, East Kolaka Regency, was a self-financing pattern using capital and costs derived from the farming actors themselves and partner financing patterns using capital and other costs borrowed through formal and non-formal institutions.